Historicism and historiosophy in Ludwig Gumplowicz’s early writings. Gumplowicz between Gobineau and Schönerer - Artico, Davide (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The research question concerns the scientific approach of Ludwik Gumplowicz to history, including the history of the pre-partition Poland, analyzed on the basis of his works written in Polish during the period preceding his final emigration to Graz in the 1870s. The paper starts with explanations reffering to some misunderstandings resulting from terminology used by Gumplowicz in his later works, such as Rassenkampf. The concept of “race” applied by Gumplowicz in his scholarly publications cannot be identified with a systematic and comprehensive racism of other authors, like anti-Semite Arthur de Gobineau or German Nationalist Georg Heinrich von Schönerer. According to Gumplowicz, “race” is a sui generis elaboration on the concept of “nation” which does not have strictly biological connotations but rather rests on historical-and-civilizational foundations. The fact of belonging to a certain “nation” does not depend — in Gumplowicz’s view — either on a biological origin or a native language but on the approbation of patterns and formulas based on and rooted in a given legal culture and legislation. In this respect, a “nation” comes into existence only when a certain community reveals a sufficient level of cultural including legal development and when — by the virtue of this development — it is capable of establishing an independent state. In this respect, a “nation” should be identified with an elite which made statehood a reality meaning nobility. On the basis of the preceding description it can be concluded that Gumplowicz’s approach to history is not inconsistent with Hegelian historicism because the emergence of “nations” is placed in a particular historical moment; after that moment “nations” will never cease to exist; therefore there is no return to a thesis in Hegelian sense when, after successfully overcoming an antithesis, a synthesis is achieved. At the same time the identification of a “nation” with aristocratic elite betrays at bottom antidemocratic convictions which are not easy to reconcile with proindependence ideas which were nevertheless adopted by Gumplowicz from Giuseppe Mazzini, with Young Poland movement serving as an intermediary.
Keywords: historycyzm; Polska; Gumplowicz, Ludwik (1838-1909); Gobineau, Arthur; Schönerer, Georg Heinrich; naród